The Relationship Between Postsecondary Education and Labour Market Outcomes: Comparing Graduates Over a Four-Cohort Period - Walters, David (My University, 2002)
Drawing on data from the 1982, 1986, 1990, and 1995 National Graduates Surveys, this dissertation win build on previous research comparing graduates of different types of postsecondary programs on various outcome measures including earnings, employment, objective and subjective over-education, and the mismatch between education and work. Particular emphasis is placed on making field of study comparisons among graduates of different levels of post-secondary schooling (i.e. trades, college, university undergraduates, professional, master's, and Ph.D.), and identifying changes over time. The central theoretical issue addressed in this dissertation involves comparing the viability of human capital theory and the credentialist perspective with respect to the relationship between post-secondary education and skins. Statistical analyses are made using ordinary least squares, ordered logistic, and multinomial logistic regression models.
Keywords: Sociology; Sociology